Achieving behaviour change at scale: Alive & Thrive's infant and young child feeding programme in Bangladesh. (May 2016) - Sanghvi, Tina; Haque, Raisul; Roy, Sumitro; Afsana, Kaosar; Seidel, Renata; Islam, Sanjeeda; Jimerson, Ann; Baker, Jean
Abstract : Abstract: The Alive & Thrive programme scaled up infant and young child feeding interventions in Bangladesh from 2010 to 2014. In all, 8.5 million mothers benefited. Approaches – including improved counselling by frontline health workers during home visits; community mobilization; mass media campaigns reaching mothers, fathers and opinion leaders; and policy advocacy – led to rapid and significant improvements in key practices related to breastfeeding and complementary feeding. (Evaluation results are forthcoming.) Intervention design was based on extensive formative research and behaviour change theory and principles and was tailored to the local context. The programme focused on small, achievable actions for key audience segments identified through rigorous testing. Promotion strategies took into account underlying behavioural determinants and reached a high per cent of the priority groups through repeated contacts. Community volunteers received monetary incentives for mothers in their areas who practised recommended behaviours. Programme monitoring, midterm surveys and additional small studies to answer questions led to ongoing adjustments. Scale‐up was achieved through streamlining of tools and strategies, government branding, phased expansion through BRAC – a local non‐governmental implementing partner with an extensive community‐based platform – and nationwide mainstreaming through multiple non‐governmental organization and government programmes. Key messages Well‐designed and well‐implemented large‐scale interventions that combine interpersonal counselling, community mobilization, advocacy, mass communication and strategic use of data have great potential to improve IYCF practices rapidly. Formative research and ongoing studies are essential to tailor strategies to the local context and to the perspectives of mothers, family members, influential community members and policymakers. Continued use of data to adjust programme elements is also central to the process. Scale‐up can be facilitated through strategic selection of partners with existing community‐based platforms and through mass media, where a high proportion of the target audience can be reached through communication channels such as broadcast media. Sustaining the impacts will involve commitments from government and capacity building. The next step for capacity building would involve understanding barriers and constraints and then coming up with appropriate strategies to address them. One of the limitations we experienced was rapid transition of staff in key positions of implementing agencies, in government leadership, donors and other stakeholders. There was a need for continued advocacy, orientation and teaching related to strategic programme design, behaviour change, effective implementation and use of data.